Municipal solid waste management in the Amazon: Environmental, social, and economic problems, gaps, and challenges - de Oliveira, Benone Otávio Souza [UNESP]; de Medeiros, Gerson Araujo [UNESP] (WITPRESS LTD., 2020)
The Amazon region presents challenges for the management of municipal solid waste (MSW), due to its social, environmental, and economic vulnerabilities. This work investigated MSW management in the Amazon and in the Southwest Brazilian Amazon (SWBRAM). A bibliographic search (from 2007 to 2019) was performed for articles published in scientific journals and in official reports, related to MSW management in the countries of the Amazon. Visits in loco to the Brazilian municipalities of Humaitá and Manicoré, in Amazonas State (AM), and Ariquemes, in Rondônia State (RO), gathered information about the characteristics of MSW (Humaitá), the conditions of a waste-collection cooperative (Manicoré), and the management of a sanitary landfill (Ariquemes). The bibliographic search found only sixteen articles, highlighting the following aspects of MSW management in the Amazon: high organic-matter content (50%) and low MSW generation. There was significant disposal of waste in dumps, an incipient recycling market, and a lack of infrastructure for logistics. The MSW management scenario for the SWBRAM was similar to that for the Amazon. In Humaitá, MSW was deposited in a dump, leading to the presence of waste pickers. In Manicoré, only plastic, paper, and aluminum could feasibly be transported on the Madeira River to the recycling industry in Manaus (AM). The high rainfall and the distance to transport MSW were the main issues related to landfill management in Ariquemes. Management actions proposed in the literature present limitations in the Amazon environment, so there is the need for continuous investment in MSW prevention programs and treatment technologies, besides optimizing recycling and composting.
Keywords: Dump; Recycling; Sanitary landfill; Waste picker